Two-year outcome comparison of custom versus conventional total knee (TKA) implants: a retrospective cohort study. Issue 5 (13th September 2022) - Passano, Brandon; Lee, Ji Won; Gallagher, Brian; Desale, Sameer; Boucher, Henry R.
Abstract : Background: Custom implants have drawn increasing interest from surgeons seeking the promise of improved coronal alignment, decreased operative time, and improved outcomes. Currently, there is no clear evidence to support those claims. This study sought to investigate whether utilization of custom implants and instrumentation would lead to a greater improvement in 2-year patient-reported outcomes compared with conventional total knee arthroplasty (TKA). Methods: This is a retrospective cohort study of 287 knees that underwent either custom TKA (n=150) or conventional TKA (n=137). Primary outcome measures included changes in Oxford Knee Score (OKS) and Short-Form 12 (SF-12) mental and physical component scores at preoperative versus 2-year follow-up. A mixed effects model was utilized to make comparisons between improvements in score. The complication and revision rates were compared. Results: There was a significant improvement in all three patient-reported outcome measures from preoperative to 2-year follow-up in both the custom and conventional instrumentation group. There were no significant differences in the magnitude of improvement between the custom and conventional groups for OKS, SF-12 mental, or SF-12 physical ( P =0.07, 0.19, and 0.13, respectively) at 2-year follow-up. There were no significant differences in the complication rate ( P =0.69) or revision rate ( P =0.60) at 2-year follow-up. Conclusions: At a minimum follow-up of 2 years, the authors found no significant differences in patient-reported outcome measures including the OKS, SF-12 mental and physical scores between custom and conventional TKAs. Additionally, there were no significant differences in complication or revision rates. Level of Evidence: Level III.